2007
DOI: 10.1152/ajpheart.00017.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning induces elevated expression of stanniocalcin-1 in the heart

Abstract: Animals exposed for a few hours to low oxygen content (8%) develop resistance against further ischemic myocardial damage. The molecular mechanism(s) behind this phenomenon, known as hypoxic preconditioning (HOPC), is still incompletely understood. Stanniocalcin-1 (STC-1) is an evolutionarily conserved glycoprotein originally discovered in fish, in which it regulates calcium/phosphate homeostasis and protects against toxic hypercalcemia. Our group originally reported expression of mammalian STC-1 in brain neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
5
32
0
Order By: Relevance
“…Previous studies showed that STC-1 was upregulated in cancer cells during hypoxia [16, 17, 38]. Our results also demonstrated that MSCs decreased apoptosis in co-cultures with a line of pulmonary epithelial cells in which apoptosis was produced by hypoxia under acidic conditions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies showed that STC-1 was upregulated in cancer cells during hypoxia [16, 17, 38]. Our results also demonstrated that MSCs decreased apoptosis in co-cultures with a line of pulmonary epithelial cells in which apoptosis was produced by hypoxia under acidic conditions.…”
Section: Discussionsupporting
confidence: 83%
“…In sections of mouse kidney, STC-1 was present throughout the cytoplasm with apparent enrichment within mitochondria [39]. In cardiomyocytes over-expressing a STC-1-FLAG fusion protein, STC-1 was seen in mitochondria [17]. STC-1 was also found in the nucleus in cardiomyocytes [40] and in mouse lactiferous duct cells during pregnancy [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multiple functions of mammalian STC1, except for the primarily reported function in fish of maintaining calcium or phosphorus homeostasis, have been demonstrated. These include ischemic tolerance in the brain or heart [40,41], regulation of cellular metabolism by targeting mitochondria [42,43] and association with angiogenesis in endothelial cells [44]. Quite recently, the presence of endometrial STC1 in pregnant mares was reported [45].…”
Section: Expression Of Stanniocalcin-1 In the Equine Endometriummentioning
confidence: 99%
“…STC1 has been identified as one of the genes regulated by HIF-1 [11]. STC1 expression induces ischemia tolerance in mouse brains and hearts, suggesting its possible role in cell survival under hypoxic conditions [12,13]. STC1 also reduces the number of apoptotic lung cancer epithelial cells following hypoxia [14], which suggests that the induction of STC1 in a hypoxic microenvironment plays an important role in tumor progression [9,11,15].…”
Section: Introductionmentioning
confidence: 99%